METHODS OF EXPRESSING DEONTIC MODALITY IN ENGLISH AND POLISH STATUTORY INSTRUMENTS IN THE ASPECT OF TRANSLATION - MATULEWSKA, Aleksandra (Comparative Legilinguistics, 2009)
This paper deals with the methods of expressing deontic modality in statutory instruments. The author analyzes three pure meanings that is to say; (i) obligation, (ii) prohibition and (iii) permission. Within those three meanings three sub-meanings are distinguished. Within the meaning of obligation, the author distinguishes the following sub-meanings: (i) unlimited duty, (ii) conditional duty, and (iii) external duty. Within the meaning of prohibition the following three sub-meanings may be distinguished: (i) unlimited prohibition, (ii) conditional prohibition, and (iii) external prohibition. Within the meaning of permission we have distinguished three sub-meanings: (i) unlimited permission, (ii) conditional permission, and (iii) external permission. The exponents of deontic modality are presented in the tables and compared in order to show potential translation equivalents.